Vertebrate lies? Arthropods were the first land animals!. (21st April 2022) - Brookfield, Michael E.; Catlos, Elizabeth J.; Suarez, Stephanie E.
Abstract : In contrast to the 'propaganda' of the currently dominant vertebrates (i.e. us), arthropods not amphibians were the first land animals. And like many another great advance, they first appeared in Scotland. The first land animals were 'millipedes', which evolved with the first true land plants at the edges of Scottish mountain lakes about 425 Ma. From then on, more elaborate and complex plant‐arthropod land communities evolved incredibly rapidly, and spread to lowland marshes, taking only 40 Myr to reach complex forest grade communities by 385 Ma. We recently dated some of the sediments enclosing these fossils to give a more precise age for the communities, a study still in progress, which indicates that the oldest land animal is a 'millipede' from Kerrera, Oban, Scotland.